Akkermansia muciniphila is associated with normal muscle mass and Eggerthella is related with sarcopenia in cirrhosis - Efremova, Irina; Alieva, Aliya; Maslennikov, Roman; Poluektova, Elena; Zharkova, Maria; Kudryavtseva, Anna; Krasnov, George; Zharikov, Yury; Nerestyuk, Yaroslav; Karchevskaya, Anna; Ivashkin, Vladimir (Frontiers in Nutrition, 2024)
Background. Sarcopenia and gut dysbiosis are common in cirrhosis. The aim is to study the correlations between the gut microbiota taxa and muscle mass level in cirrhosis.. The study included 40 cirrhosis patients including 18 patients with sarcopenia. The gut microbiota composition was assessed using amplicon sequencing of the hypervariable V3-V4 regions of the 16S rRNA gene. The skeletal muscle mass, subcutaneous and visceral fat levels were assessed with abdominal computed tomography as skeletal muscle, subcutaneous and visceral fat indices (SMI, SFI and VFI). Results. Patients with sarcopenia had more relative abundance (RA) of Agathobacter, Anaerostipes, Butyricicoccus, Dorea, Eggerthella, Microbacteriaceae, Veillonella and less RA of Akkermansiaceae, Akkermansia muciniphila, Verrucomicrobiae and Bilophila compared to patients with normal muscle mass. SMI directly correlated with RA of Akkermansia, Alistipes indistinctus, Anaerotruncus, Atopobiaceae, Bacteroides clarus, Bacteroides salyersiae, Barnesiellaceae, Bilophila wadsworthia, Pseudomonadota, Olsenella, and Parabacteroides distasonis, and negatively correlated with RA of Anaerostipes and Eggerthella. Sarcopenia was detected in 20.0% patients whose gut microbiota had Akkermansia but not Eggerthella, and in all the patients, whose gut microbiota had Eggerthella but not Akkermansia. The Akkermansia and Eggerthella abundances were independent determinants of SMI. RA of Akkermansia,